Phase 2 Randomized Study of Oral Ibrexafungerp Versus Fluconazole in Vulvovaginal Candidiasis. (23rd September 2021) - Nyirjesy, Paul; Schwebke, Jane R; Angulo, David A; Harriott, Itzel A; Azie, Nkechi E; Sobel, Jack D
Abstract: Background: Vulvovaginal candidiasis affects approximately 75% of women in their lifetime. Approved treatment options are limited to oral or topical azoles. Ibrexafungerp, a novel, first-in-class oral triterpenoid glucan synthase inhibitor, has demonstrated broad fungicidal Candida activity and a favorable tolerability profile. The primary objective of this dose-finding study was to identify the optimal dose of oral ibrexafungerp in patients with acute vulvovaginal candidiasis. Methods: Patients with vulvovaginal signs and symptoms score ≥7 were randomized equally to 6 treatments groups: 5 treatment doses of oral ibrexafungerp or oral fluconazole 150 mg. The primary endpoint was the percentage of patients with a clinical cure (complete resolution of vulvovaginal signs and symptoms) at the test-of-cure visit (day 10). Results: Overall, 186 patients were randomized into the 6 treatment groups. Results, using the modified intent-to-treat population (baseline positive culture), are reported for ibrexafungerp 300 mg twice daily (BID) for 1 day (n = 27), which was the dose selected for phase 3 studies, and fluconazole 150 mg for 1 day (n = 24). At day 10, the clinical cure rates for ibrexafungerp and fluconazole were 51.9% and 58.3%, respectively; at day 25, patients with no signs or symptoms were 70.4% and 50.0%, respectively. During the study ibrexafungerp patients required less antifungal rescue medications compared with fluconazole (3.7% vs 29.2%, respectively). Ibrexafungerp was well tolerated, with the most common treatment-related adverse events being mild gastrointestinal events. Conclusions: Ibrexafungerp is a well-tolerated novel antifungal with comparable efficacy to fluconazole in the treatment of acute vulvovaginal candidiasis. Clinical Trials Registration: NCT03253094 Abstract : Single-day ibrexafungerp treatment, the first in a new class of fungicidal drugs, is well tolerated and provides similar efficacy to single-dose fluconazole 150 mg for acute vulvovaginal candidiasis.